Analisis Kemampuan Representasi Matematis dalam Menyelesaikan Soal AKM berdasarkan Motivasi Belajar dan Rumpun Bidang Ilmu Siswa SMA - Musafaah, Rizki Yahrulaji; Wahidin, Wahidin (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2022)
The goals of this research is to analyst representation ability in solving minimum assessment competence question base on studying motivation and high school knowledge class. Research method used is qualitative with descriptive analysis technique. The research subject is second grade of highschool from science, social, and language classes from two different region school include SMA from Kota and SMA from Kabupaten. This research subject from two school is 447 student, 282 from Kota, and 165 From Kabupaten while the research subject of minimum assessment competence question is 3 student from each school Kota and Kabupaten. The stages of selecting research subject from the result of filling out a learning motivation questionnaire with high, medium, and low levels. Research technique used studying motivation questionnaire, instrument test, and interview. Data analysis techniques used in this study are dara collection, data reduction, data presentation, and drawing conclusions. There is 4 skill indicator in this research that representative mathematic and 6 studying motivation indicator. Result of this research region SMA from Kota is 22 student had low study motivation, 258 student had average study motivation, and 2 student had high study motivation, while region SMA from Kabupaten is 17 student had low study motivation, 146 student had average study motivation, and no one student had high study motivation. Meanwhile result of mathematic representative skill test can assume from this research, mathematic representative ability of student in Kota is higher in student from Kabupaten. And the mathematical representation ablity of student in science student is superior to social student and language student.